Capsazepine affects thermal preferences of the American cockroach (Blattodea: Blattidae) - Justyna MALISZEWSKA (European Journal of Entomology, 2016)
Capsazepine is a competitive antagonist of capsaicin, a TRPV1 agonist responsible for the spicy taste of pepper. TRPV1 agonists and antagonists are known to affect mammalian body temperature, but their action on thermoregulation in insects is poorly known. In this study we evaluated the effect of capsazepine on the thermal preference of the American cockroach, Periplaneta americana using a thermal gradient. Our results revealed that capsazepine in submicromolar concentrations induces a preference for higher ambient temperatures when compared to the control insects. To assess whether capsazepine may act also as an antagonist of capsaicin in insects, we determined this insects' thermal behaviour when capsazepine was applied before capsaicin. The hypothermic response to capsaicin was clearly blocked by pre-treatment with capsazepine only in female American cockroaches. Our results indicate the involvement of structures functionally similar to TRPV1 in insect thermosensation.